Bone health education booklet: a guide for women living with menopause - Nik Mohd Hatta, Nik Noor Kaussar; Md Isa, Muhammad Lokman; Nurumal, Mohd Said (2020)
This booklet is an outcome from the research which tends to guide post-menopausal women in maintaining their bone health throughout menopausal life. This booklet consists of 12 sections with the full of information regarding the information about bone, bone screening, nutritional, exercise and fall prevention strategies.